Expertise in Mathematics Instruction
XVIII, 372 p.
Keywords: Expertise in Mathematics Instruction An International Perspective Yeping Li, Gabriele Kaiser, editors While the concept of the expert educator is far from being new, and the process of acquiring expertise as an instructor has long been of interest to researchers, the specifics of expertise in the teaching of mathematics remain difficult to describe it theoretically and to evaluate it empirically. To improve this situation, Expertise in Mathematics Instruction takes a unique approach to present new research from multiple Western and Eastern countries, offering a comprehensive picture of the components making up this elusive competency, and how these elements contribute to the teaching process in different educational systems and cultural contexts. The book is organized to probe three universal themes: identifying expert teachers, specifying and analyzing teacher expertise in mathematics education, and understanding expertise in mathematics education as it is perceived and valued in different cultures. From this richly inspiring collection, readers may better understand—and possibly rethink—their own policies and practices as mathematics educators, teacher educators or researchers. Some highlights of the volume: • Roles of the expert mathematics teacher envisioned in the West and the East. • Profiles of teacher expertise in mathematics instruction identified in the East and West. • Enabling a significant role for students in classroom discourse. • Developing expertise in using textbooks to teach mathematics. • Cross-national comparative results on teachers’ qualifications and practices. Expertise in Mathematics Instruction brings invaluable insights to mathematics educators and teacher educators who wish to help teachers improve their competence, and to researchers studying this critical aspect of mathematics pedagogy.